Controlled Co-delivery of pPDGF-B and pBMP-2 from intraoperatively bioprinted bone constructs improves the repair of calvarial defects in rats. (February 2022) - Moncal, Kazim K.; Tigli Aydın, R. Seda; Godzik, Kevin P.; Acri, Timothy M.; Heo, Dong N.; Rizk, Elias; Wee, Hwabok; Lewis, Gregory S.; Salem, Aliasger K.; Ozbolat, Ibrahim T.
Abstract: Intraoperative bioprinting (IOB), which refers to the bioprinting process performed on a live subject in a surgical setting, has made it feasible to directly deliver gene-activated matrices into craniomaxillofacial (CMF) defect sites. In this study, we demonstrated a novel approach to overcome the current limitations of traditionally fabricated non-viral gene delivery systems through direct IOB of bone constructs into defect sites. We used a controlled co-delivery release of growth factors from a gene-activated matrix (an osteogenic bioink loaded with plasmid-DNAs (pDNA)) to promote bone repair. The controlled co-delivery approach was achieved from the combination of platelet-derived growth factor-B encoded plasmid-DNA (pPDGF-B) and chitosan-nanoparticle encapsulating pDNA encoded with bone morphogenetic protein-2 (CS-NPs(pBMP2)), which facilitated a burst release of pPDGF-B in 10 days, and a sustained release of pBMP-2 for 5 weeks in vitro . The controlled co-delivery approach was tested for its potential to repair critical-sized rat calvarial defects. The controlled-released pDNAs from the intraoperatively bioprinted bone constructs resulted in ∼40% bone tissue formation and ∼90% bone coverage area at 6 weeks compared to ∼10% new bone tissue and ∼25% total bone coverage area in empty defects. The delivery of growth factors incorporated within the intraoperatively bioprinted constructs could pose as an effective way to enhance bone regeneration in patients with cranial injuries in the future.